MEMBANGUN STRATEGI BISNIS MELALUI FAKTOR MANAJERIAL SEBAGAI PEMILIK DAN LINGKUNGAN BISNIS EKSTERNAL DALAM MENINGKATKAN KINERJA - Wardi, Yunita Kusuma; Mangunwihardjo, Suyudi; Perdana, Mirwan Surya (JURNAL BISNIS STRATEGI, 2016)
he pupose of this research is to build a business strategy through managerial factors as the owner and external business environment in improving corporate performance (Studies on food SMEs in Semarang).Samples were SMEs food in the city, a total of 106 respondents. Structural Equation Model (SEM) was run by AMOS software was used to analyze the data. The analysis showed that the business strategy through managerial factors as the owner and external business environment positive effect in improving corporate performance.The empirical findings indicate that factors managerial positive influence on business strategy, the external environment has positive influence on business strategy, managerial factors have positive influence on the performance of the company. The external environment is not positive effect on the company's performance and business strategy did not affect the company's performance.